Vacancies and Labour Demand in Russia: Regional Patterns and Key Influencing Factors - Korshunov , Ilya A.; Shirkova , Natalia N.; Nazarov , Mikhail G. (Economy of Regions, 2025)
Understanding labour market dynamics and trends in Russia is essential for effective policy-making in the sphere of human resource management. This article analyses the impact of staff turnover, investment activity, and regional economic development on the number of vacancies posted on the Rabota Rossii recruitment platform. Using descriptive statistics and regression analysis, the study identifies how these factors influence labour demand across different regions. The findings highlight distinct regional and sectoral patterns: economically weaker regions tend to have more labour market stability and slower job creation, while more developed regions demonstrate a continuous creation of new jobs with large workforce numbers, which also leads to higher staff turnover. The data also show that vacancies for new positions are fewer than those for replacing existing staff. Data from recruitment websites confirm that regions with higher job creation rates tend to have a higher gross regional product per capita, reflecting stronger production, better-quality output, greater economic activity, and more opportunities to attract new investors and entrepreneurs. The study provides a practical framework for analysing regional labour demand, which can be of interest to employers seeking to improve recruitment strategies and to local authorities aiming to enhance employment support programs and labour market development.